Penerapan Model Pembelajaran Inkuiri Terbimbing Berbasis Chemo-Edutainment untuk Meningkatkan Pemahaman Konsep Murid pada Materi Hidrolisis Garam XI SMAN 2 Siak Hulu - Eva Refita; Lenny Anwar; Dedi Futra (Lembaga Yasin AlSys, 2026)
Students’ conceptual understanding of salt hydrolysis remains relatively low because of the abstract nature of the material and learning that does not yet fully involve students actively. This study aims to determine the effect of implementing the Guided Inquiry learning model based on Chemo-Edutainment on improving students’ conceptual understanding of salt hydrolysis. This study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Pretest–Posttest Design. The research sample consisted of two Grade XI MIPA classes at SMAN 2 Siak Hulu selected using purposive sampling, namely the experimental class, which received Guided Inquiry learning based on Chemo-Edutainment, and the control class, which received Guided Inquiry learning. Data were collected through conceptual understanding tests in the form of a pretest and posttest, then analyzed using normality tests, homogeneity tests, t-tests, and N-Gain. The results showed a significant difference in the improvement of conceptual understanding between the experimental class and the control class, with a calculated t-value of 9.957 > table t-value of 1.996 at a significance level of 0.05. The experimental class obtained an N-Gain score of 0.74 in the high category, whereas the control class obtained an N-Gain score of 0.64 in the moderate category. The conclusion of this study affirms that the implementation of the Guided Inquiry learning model based on Chemo-Edutainment is effective in improving students’ conceptual understanding of salt hydrolysis. The implications of this study indicate the importance of chemistry learning that integrates scientific inquiry processes and enjoyable educational activities to improve the quality of conceptual understanding, particularly in abstract chemistry topics.